Adult-Onset Severe Hypocalcemia Due Defect in Parathyroid Calcium-Sensing Receptors - El-Reshaid, Kamel; Al-Bader, Shaikha (International Journal of Innovative Research in Medical Science, 2020)
Parathyroidectomy, of the 4 glands, with/without thyroidectomy is the most common cause of hypoparathyroidism. Autoimmunity is a rare etiology, either as an isolated endocrinopathy or as a component of autoimmune polyglandular syndrome 1 (APS 1). In this case report; we describe a patient with an adult-onset hypoparathyroidism and discuss its pathophysiology in relation to calcium-sensing receptors in addition to its diagnostic work up and management.